Analisis Peran Kebijakan Fisikal Dalam Mengatasi Ketimpangan Ekonomi Di Negara Berkembang - Zai, Septiniat; Sabailaket, Ani Susanti (Jurnal Ilmu Ekonomi dan Bisnis, 2024)
Economic inequality is a significant challenge for developing countries, hampering inclusive growth and sustainability. This study aims to analyze the role of fiscal policy in addressing economic inequality, focusing on income redistribution through progressive taxation, public spending, and social transfers. The research method used is a quantitative approach with secondary data from national and global economic reports, as well as regression statistical analysis to evaluate the relationship between fiscal policy and inequality indicators, such as the Gini Index and absolute poverty. The results show that fiscal policies, especially in the form of progressive taxation and targeted social spending, have a positive impact on reducing economic inequality in developing countries. However, the effectiveness of these policies varies among the countries studied, depending on the level of corruption, the efficiency of fiscal administration, and the prioritization of public spending. Some countries with high levels of inequality show that inefficient public spending and budget leakages exacerbate inequality. The discussion highlights the importance of improving fiscal governance and strengthening tax administration capacity to enhance the redistributive impact of fiscal policy. In addition, fiscal policy needs to be tailored to the local context to ensure social justice and equal economic opportunity. In conclusion, effectively designed fiscal policies can play an important role in reducing economic inequality in developing countries. However, the success of these policies depends on good management and political commitment to sustainably improve resource distribution.